المشتقات في سورة الاعراف - عبد الرحمن زايد ايناس (Al-Adab Journal, 2018)
The most important conclusion I reach in my research that particle from in Area I sure is mentioned eighty four times as a plural for masculine exaggeration from such us Gater (forgiver) , Raheem (merciful) , Gofer (forgiver) and Manan (granter) are metaphor . They are subject of exaggeration and have no exaggeration because exaggeration is the adjectives that is attributed to who does not have and Allah features are highest in perfection and were not exaggerated . Also exaggeration is the ejective accept addition and reduction and Allah features are deem for above – similar feature is taken from intransitive verb to indicate on a meaning stands for the adjective in approved way… and has no time for it , The things that need time are the temporary objectives and are measured without triple weighted on participle in condition that the meaning is on continuous from for difference between these two objectives . The participial comes with the forming Arraf sura from the triple as in Quran (say get out from it dispraised and the form on objective meaning is this sura is (Doer , Done) fael , feil . fa’al , faeel , faala , faool , foela , folaho . The adverbs have their form from the triple on Mofal , Mofel and on past participle without triple.